Creating awareness on food science and technology in PERTEMA sharing - UiTM, Faculty of Applied Sciences (Faculty of Applied Sciences, 2021)
The objectives of this programme are to improve students’ knowledge, creativity and digital skills by selecting appropriate information related to food science in creating quality posters.